Teacher-Trainee Preparedness on Integration of ICT for Instruction in Selected Public Teacher Training Colleges in North Rift, Kenya - Kipsaina, Katam Joseph; Jepchirchir, Kosgei Joan; Boit, Kemboi Mary (Advances in Social Sciences Research Journal, 2017)
ICT is a very a very powerful medium of instruction in contemporary pedagogical processes. The aim of this study was to investigate teacher-trainee preparedness on the integration of ICT for learning in selected public teacher training colleges in North Rift, Kenya. The specific objectives were; to find out Teacher-Trainee planning process for use of ICT in teaching, determine teacher-trainee perception on integration of ICT in teaching and learning and to assess the teacher trainees’ use of e-materials during learning process. The study was guided by Davis’ Technology Acceptance Model (TAM). Descriptive research design and mixed method approach was used in this study. This study used questionnaires, document analysis and observation as instruments of collecting data. Slovin's formula was used to obtain a sample of 352 respondents from a target population of 2946 respondents. Purposive sampling was used to select three colleges and 2nd year students. Proportionate simple random sampling technique was used to select teacher trainees from the cohort of the 2nd year students. The questionnaire was face validated by education experts while the reliability was established by piloting the research instruments through test re-retest method. A Pearson Product Moment Correlation reliability coefficient of 0.8 was obtained indicating that the instrument was reliable. Descriptive statistics was used to analyze the data obtained and results presented in frequencies and percentages. The study findings showed that majority of the teacher trainees used ICT in searching teaching and learning materials. Majority of teacher trainees believed that ICT helped in lesson preparation. Majority of the teacher trainees believed that they updated content of their subject areas through the internet. It also emerged that majority of the teacher-trainees believed that ICT had positive effect on the quality of teaching and learning. Majority of the teacher trainees believed that ICT could enhance students’ participation and feedback to teacher. Teacher-trainees occasionally used ICT applications during learning process. It was therefore concluded that teacher trainees needed basic skills in computer applications and that computer equipments be availed to all students for use in teaching and learning process. It was recommended that ICT be integrated into teacher education programmes to ensure adequate preparedness for classroom instruction.